Association between a combination of cognitively stimulating leisure activities and long-chain polyunsaturated fatty acid intake on cognitive decline among community-dwelling older Japanese individuals - Tokuda, Hisanori; Horikawa, Chika; Nishita, Yukiko; Kaneda, Yoshihisa; Obata, Hidenori; Rogi, Tomohiro; Izumo, Takayuki; Nakai, Masaaki; Shimokata, Hiroshi; Otsuka, Rei (Frontiers in Aging Neuroscience, 2024)
Multifactorial lifestyle approaches could be more effective than a single factor for maintaining cognitive function. This study investigated the association of combining cognitively stimulating leisure activities (CSLA), including puzzles, quizzes, and cognitive training games, with intake of long-chain polyunsaturated fatty acids (LCPUFA), including docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and arachidonic acid (ARA), on cognitive function in the older Japanese individuals without dementia. Participants were community-dwelling Japanese individuals without a self-reported history of dementia (n = 906, aged 60-88 years) from datasets of a 2-year longitudinal study (baseline: 2006-2008 and follow-up: 2008-2010). CSLA engagement and LCPUFA intake were divided into high and low groups according to frequency (≥once/week and